2020
DOI: 10.1080/16878507.2020.1789388
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on astaxanthin recovery from shrimp wastes using lactic fermentation and green solvents:an applied model on minced Tilapia

Abstract: El-Khalek (2020) A comparative study on astaxanthin recovery from shrimp wastes using lactic fermentation and green solvents:an applied model on minced Tilapia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Fermentation continued by an extraction process using green solvents is an eco-friendly and straightforward method to recover astaxanthin from shrimp (Cheong et al, 2014;El-Bialy and El-Khalek, 2020). An essential issue in the recovery of astaxanthin from shrimp shells is the initial water content (Hu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation continued by an extraction process using green solvents is an eco-friendly and straightforward method to recover astaxanthin from shrimp (Cheong et al, 2014;El-Bialy and El-Khalek, 2020). An essential issue in the recovery of astaxanthin from shrimp shells is the initial water content (Hu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Water activity affecting shelf-life, fat oxidation, protein denaturation, and vitamin degradation. Alla El-Bialy and Abd El-Khalek [ 44 ] found that the addition of astaxanthin preparations to tilapia meat reduced a w by 0.05 and this effect was maintained for 20 days of storage; however, phenomena in fish meat can be different than this one in tvarog. Statistical analysis showed that there was no correlation between moisture and a w in the tvarogs.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of ALP prolonged the acidity stabilization time in the ACCs by one week (to the 3rd week). This may indicate the bacteriostatic properties of astaxanthin against lactic acid bacteria [ 44 ]. During 4 weeks of storage, the acidity least increased by 0.3% in the ACC containing 0.5% ALP, while it increased by 0.5–0.6% in the other samples.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical methods produce abundant yield, but the process is crippled by the side effects associated with the various chemical (Biao and Kaijin 2007 ). Due to their low metabolic activity, biological methods produce lower yields than chemical methods (El-Bialy and Abd El-Khalek 2020 ; Cabanillas-Bojórquez et al 2021 ). One of the reasons for the poor standardization of chitin and chitosan is they are fundamental.…”
Section: Sw In the Production Of Animal Feedmentioning
confidence: 99%